The specification of the growing temperature on PDA of chestnut blight pathogen (Cryphonectria parasitica (Murr.) Barr) to optimize timing for biocontrol treatments by hypovirulent strains - Kovács, Gabriella; Radócz, László (Acta Agraria Debreceniensis, 2017)
The most destructive pathogen for the European chestnut trees is the blight fungus Cryphonectria parasitica (Murr.) Barr. The biological control is the only effective possibility to apply in situ biocontrol by hypovirulent strains against compatible virulent (wild) fungus strains. The infested bark tissues can inoculate by drilling holes surrounding and putting into agar discs interwoven by the appropriate vegetative compatible group (VCG) hypovirulent fungus strains. This latest can pass those virus-like particles (VLPs) by parasexual contact (called hypha-anastomosis)which responsible to hypovirulence. A laboratory experiment was made to find the optimal times to carry out the treatments. The intensity of growth of fungal colonies were analysed on different temperatures. The growth of the fungus on low temperature were rather slow,according to our expectations. On higher temperature the colony progress were the same as on the optimal 20–25 °C. These observations and the environment determine the date of the field applications under Hungarian weather conditions. It means the optimal treatment periods can be May or end of September to middle October in Hungary.